Exploring factors influencing technology adoption rate at the macro level: A predictive model. (February 2022) - Hooks, D.; Davis, Z.; Agrawal, V.; Li, Z.
Abstract: Technology adoption is crucial to economic growth, yet levels of technology adoption vary, with limited adoption in many countries. Countries wield considerable technology adoption power and their adoption activities can be leveraged to achieve social, economic, and environmental goals by endorsing specific technologies. To encourage greater adoption, it is vital to determine the predictors of technology adoption to design effective promotion policies, accomplished through the modification of Diffusion of Innovation theory. While there is substantial research in individual consumer adoption behavior, less is known about country level factors that impact technology adoption. To overcome these gaps in the research, we undertook an investigative study to better understand the predictors of a country's technology adoption rate. We use a random effects panel model to predict technology adoption factors for a sample of 15 countries over the period of 2010–2019 using secondary datasets. We identify a statistically significant effect of competitiveness, cybersecurity, ease of doing business, and the level of political stability/non-violence and terrorism. We thus posit that a country that is highly competitive, has enhanced cybersecurity, is easy to do business in, and has a low level of political violence and terrorism adopts new technologies more readily than others. Highlights: Technology adoption rate at a macroeconomic level is significantly effected by competitiveness, cybersecurity, and the level of political stability/non-violence and terrorism. Findings include that Countries that are highly competitive, have enhanced cybersecurity and a low level of political violence and terrorism adopts new technologies more readily than others. As technology evolves, countries must divert attention away from intrinsic technology investments and incorporate several technological components into a more streamlined adoption.